How Has the COVID-19 Pandemic Been Driving the Slowbalisation Process? - Anna ODROBINA (Communications of International Proceedings, 2021)
The global economic crisis caused by the COVID-19 pandemic has contributed to the structural changes in the globalisation process observed in the aftermath of the financial crisis of 2008–2009, characterised by slowdown in the internationalisation of economic activities. Scientific discussions increasingly considered an emerging new wave of globalisation, in the form of slowbalisation. The article aims to establish the impact of the pandemic on the course of slowbalisation. It seems that the consequences of the pandemic have had and will continue to have a crucial influence on the future of globalisation as the pandemic has been causing significantly more far-reaching effects than simply a shock contraction in international economic activities as a result of the economic crisis. Deep structural transformations concern the functioning of international business (including the reconfiguration of supply chains), global trade in goods and services, capital flows. Dramatic changes can be observed in geopolitics, in the form of increased protectionism and interventionism, promoting economic self-sufficiency. As demonstrated by the research results, all the symptoms of slowbalisation, gradually coming to light in 2011–2019, have been particularly reinforced by the pandemic; those changes are likely to continue and fuel an even stronger slowbalisation trend in the world economy.
Keywords: Globalisation; Pandemic; International Trade; FDI; GVC; International Production; Geopolitics; Digitalisation.